2013
DOI: 10.5588/ijtld.12.0627
|View full text |Cite
|
Sign up to set email alerts
|

Cost utility of lateral-flow urine lipoarabinomannan for tuberculosis diagnosis in HIV-infected African adults

Abstract: Setting Inpatient hospitals in South Africa and Uganda Objective To evaluate the cost-effectiveness of a lateral flow urine lipoarabinomannan (LAM) test when added to existing strategies for tuberculosis (TB) diagnosis in HIV-infected adults (CD4+ T-cell counts<100 cells/μL) with symptoms of active TB. Design Decision-analytic cost-utility model with the primary outcome being the incremental cost-effectiveness ratio (ICER), expressed in 2010 US dollars per disability-adjusted life year (DALY) averted, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
(16 reference statements)
2
35
0
Order By: Relevance
“…A cost-utility analysis restricted to hospitalized, severely immunocompromised, HIV-infected African adults showed that the addition of lateral flow urine LAM testing to standard tuberculosis diagnostics detected additional TB cases at an incremental cost in US dollars per disability-adjusted life year averted of USD $86 in Uganda and USD $353 in South Africa, and was therefore likely to be cost-effective in those populations. 36 Finally, while we purposefully sought diversity within our study population, our findings may not apply to all other populations, especially those with less advanced immunosuppression and/or less severe tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
“…A cost-utility analysis restricted to hospitalized, severely immunocompromised, HIV-infected African adults showed that the addition of lateral flow urine LAM testing to standard tuberculosis diagnostics detected additional TB cases at an incremental cost in US dollars per disability-adjusted life year averted of USD $86 in Uganda and USD $353 in South Africa, and was therefore likely to be cost-effective in those populations. 36 Finally, while we purposefully sought diversity within our study population, our findings may not apply to all other populations, especially those with less advanced immunosuppression and/or less severe tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
“…Key parameters including disease prevalence and diagnostic test performance are summarized in Table 1 and Supplemental Digital Content 1, http://links.lww.com/QAD/A400 [3,9,10,12,14,16–37]. Data were collected during a prospective study comparing the sensitivity and specificity (stratified by CD4 + cell count) of the urine LF-LAM assay, Xpert MTB/Rif, and combinations of tests among HIV-infected patients presenting with signs or symptoms of TB [12] [NCT01525134].…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al [14] recently showed that usage of LF-LAM for hospitalized patients with low CD4 + cell count in South Africa was considered highly cost-effective compared with smear-microscopy alone. The cost-effectiveness of incorporating LF-LAM testing as part of diagnostic algorithms with or without Xpert for a broader population of HIV-infected individuals, including outpatients and those with less immunosuppression, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…59,79,80 Integrating TB screening methods (e.g., Xpert MTB/RIF or urine LAM) when initiating ART for PLHIV can be cost-effective in South Africa, as compared to symptom screening and sputum smear or sputum culture. 81-83 Point-of-care tests that improve linkage to care could outweigh limitations in test characteristics, such as reduced sensitivity or specificity, when compared with a laboratory-based test. 84 Isoniazid preventive therapy among PLHIV offers another example of how integrating an aspect of TB prevention into HIV services can be cost-effective.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%